‘Good’ Things Take Time: A Living Story of Research As ‘life’ - Hurd, F; Dyer, S; FitzPatrick, M (Emerald, 2019)
Purpose Although the process of fieldwork is often characterised by dis-order, the requirement to adhere to a tightly defined methodology and produce timely research outputs often leads us to present our findings as though the research has been the product of a linear process. In this paper, we unmask this paradox, by documenting the dis-order and development of a research project 15 years (so far) in duration. Design/methodology/approach The approach used in this article is one of autoethnographic reflection, drawing on aspects of Boje’s living story approach, incorporating not only the ‘linear’ narrative of the research process, but also fragments of ante-narrative, themes running above and below the dominant. Within the study we are reflecting on, we employ a range of qualitative methods, including interview, focus groups, memory work, and living story (ante narrative) methods, within a critical management research methodology Findings Our experiences show that although ‘messiness’ may be an inherent part of qualitative research, it is this very dis-order, and the consequent opportunities for time and space, that allows the research, and the researcher, ‘time to breathe’. This reflexivity allows for methodological development and refinement, and ultimately rigorous and participative research, which also honours our participants. We argue that although this approach may not align with the current need for prolific (and rapid) publication, in allowing the dis-order to ‘be’ in the research, and allowing the time to reassess theoretical and methodological lenses, the resultant stories may be more authentic - both the stories gathered from participants and the stories of research. Originality/value The paper highlights the intertwining of stories of participants and stories from research, which is a significant addition to understandings of the ‘messiness’ of qualitative research. This paper adds to the growing call for the inclusion of ‘chaos’ and authenticity in qualitative research, acknowledging and valuing the humanity of the researcher, and giving voice to the paradox between the time to methodologically develop, and the requirement for timely research.
Keywords: Fieldwork; Stories; Disorder; Research risks; Reflexivity